Analisis Determinan Kemiskinan Di Provinsi Aceh Dengan Pertumbuhan Ekonomi Sebagai Variabel Intervening - Yusniar, Dicky Wayus; Talia Jesika Berutu; Sri Asmaul Husna; Asnidar; Ahmad Ridha (IAIN Langsa, 2024)
Poverty in Aceh Province is a multidimensional problem that is influenced by education, health, and labor force participation. This study aims to analyze the effect of average years of schooling, life expectancy, and labor force participation rate on poverty, either directly or through economic growth as a mediating variable. The data used is secondary data from 2011-2023 which is analyzed using path analysis techniques. The results show that average years of schooling have a significant negative effect on poverty, both directly and indirectly through economic growth. In contrast, life expectancy and labor force participation rate do not show a significant effect on economic growth and poverty. Economic growth, although fluctuating, does not significantly affect the poverty rate in Aceh Province. These findings emphasize the importance of improving education as a key poverty alleviation strategy and the need for formal sector development to maximize labor force participation.